Instrukcje rodzicielskie Wacława Rzewuskiego dla syna Seweryna oraz córek Teresy i Ludwiki z lat 1754 i 1763/64 - Kucharski, Adam (Biuletyn Historii Wychowania, 2017)
Parental instructions of Wacław Rzewuski for his son Seweryn and daughters from the years 1754 and 1763/64 The education of younger generations had long and rich traditions in the old Polish aristocratic Rzewuski family. The domestic and foreign education of sons in particular played a major role in building the power and social position of the family. The main purpose of this article is to present hitherto unknown sources on the history of the education of members of this family. Between 1754 and 1763 (or 1764) four instructions have survived, written by Wacław Rzewuski for his son Seweryn and two daughters: Teresa Karolina and Ludwika Maria Róża. The first instruction for Seweryn Rzewuski comes from the period of his studies in Warsaw (1754), when the young magnate attended the college of Theatines. In this piece of writing, the father gives detailed instructions on the civic education for his son. This instruction contains advice on how to behave properly during social gatherings and religious ceremonies. It also refers to the rules of the moral education of the young boy. The second instruction for Seweryn contains advice on the protection of the family residences in Podhorce and Olesko and was associated with the political situation in which Waclaw Rzewuski and his sons lived in the years from 1763-1764. However, the two instructions for his daughters are a real rarity. Wacław Rzewuski paid great attention to their security and safety and very good presence. One of the instructions was devoted to the conditions and circumstances for short journeys by the daughters to a nearby church or monastery. In particular, it concerns the staff of the daughters’ traveller suite. Another talks about being cautious with fire during their stay in the palace in Podhorce. Both instructions are unique documents of the realities of daily life and domestic trips by young women from the aristocratic sphere, and a father’s expectations with regard to their proper behaviour and maintaining good manners.